Mutations of domain V in 23S ribosomal RNA of macrolide-resistant Mycoplasma gallisepticum isolates in Egypt - Ahmed M Ammar; Norhan K Abd El-Aziz; Ahlam A Gharib; Hanaa K Ahmed; Amira E Lameay (Journal of Infection in Developing Countries)
Introduction: Avian mycoplasmas impose a significant economic burden to the poultry industry. In recent years, macrolide-resistant Mycoplasma gallisepticum have occasionally been encountered in Egypt. Methodology: This study was designed to document the involvement of macrolide-resistant M. gallisepticum in respiratory organs of chickens suffering respiratory problems. Concurrently, an exhaustive molecular characterization of the intrinsic resistance of recovered isolates to macrolides was done. Results: Of 120 chickens showing respiratory problems, 14 (11.67%) M. gallisepticum were isolated and genetically identified; 8 of them were recovered from air sacs, 4 from lungs, and 2 from tracheas. Broth microdilution of all M. gallisepticum isolates showed various degrees of minimum inhibitory concentrations (MICs) against macrolides: erythromycin (0.25–32 µg/mL), tylosin (0.0625–4 µg/mL), and tiamulin (0.031–2 µg/mL). Nucleotide sequencing of domain V (peptidyl transferase region) of the 23S rRNA gene of macrolide-resistant M. gallisepticum isolates revealed transition mutations at positions 2068 and 2069 (corresponding to 2058 and 2059 in Escherichia coli numbering) in an isolate and at position 2067 (corresponding to 2057 in E. coli numbering) in three isolates as hot spots for macrolide resistance. Surprisingly, a transversion mutation at position 2621 (corresponding to 2611 in E. coli numbering) was reported in one of the recovered isolates as a first report. Conclusion: Generation of new mutations is evidence for persistence of M. gallisepticum despite macrolide treatment. Periodic surveys to monitor for the possible appearance of resistant strains are recommended.